Lecciones sobre la verruga peruana o "enfermedad de Carrión" - Arce, Julián (1918)
Peruvian wart or Carrion's disease, took place between singular tropical diseases, not only for its extremely limited geographic distribution, but also by their clinical appearance anatomical feature, which can be synthesized from now, in the next two syndromes: anemia and eruption.